Inside Cover: Nb‐Doped Hematite Nanorods for Efficient Solar Water Splitting: Electronic Structure Evolution versus Morphology Alteration (ChemNanoMat 7/2016). Issue 7 (27th June 2016) - Fu, Yanming; Dong, Chung‐Li; Lee, Wan‐Yi; Chen, Jie; Guo, Penghui; Zhao, Liang; Shen, Shaohua
Abstract : Hematite (α‐Fe2 O3 ) nanorods were doped with Nb via a solution‐growth method, in which the electronic structure evolution and morphology alteration depended greatly on the dopant concentrations. The strong enhancement in photoelectrochemical activity induced by moderate Nb doping was attributed to the increased charge carrier density for promoted charge transfer ability as well as the smaller nanorod diameter for shortened charge‐transfer distance. This study demonstrates doping could be an effective way to develop efficient α‐Fe2 O3 ‐based photoelectrodes for solar water splitting, and that the synergetic optimization of morphology and electronic structure must be taken into consideration. More information can be found in the Full Paper by S. Shen et al. onpage 704 in Issue 7, 2016 (DOI:10.1002/cnma.201600024 ).